Female Founders in Byzantium and Beyond - Theis, Lioba (2013)
This volume presents the results of a scholarly meeting which focused on the patronage of women in the Byzantine Empire. In their scope, the articles address broadly not only the founding or re-founding of churches and monasteries, but also their rich decoration, as well as numerous smaller donations. In spite of increased attention to gender research in recent years, a comparative treatment of the legal and economic potentiel that women in Byzantium could exercise in order to exert independent influence has been lacking; thus a gender-specific viewpoint for the volume was intentionally chosen.